Highly efficient photovoltaics and field-effect transistors based on copolymers of mono-fluorinated benzothiadiazole and quaterthiophene: synthesis and effect of the molecular weight on device performance1. Issue 33 (7th September 2015) - Hao, Minghui; Li, Xiaodong; Shi, Keli; Xie, Dongjun; Zeng, Xuan; Fang, Junfeng; Yu, Gui; Yang, Chuluo
<x xml:space="preserve">Abstract</x> A D–A conjugated polymer based on mono-fluorinated benzothiadiazole (FBT) was designed and synthesized, and high performance photovoltaics and FETs were achieved.